Comparison of Anion‐Anion Halogen Bonds with Neutral‐Anion Halogen Bonds in the Gas Phase and Polar Solvents. Issue 2 (5th February 2021) - Li, Ying; Meng, Lingpeng; Zeng, Yanli
Abstract: In recent years, anion‐anion halogen bonds and neutral‐anion halogen bonds have received extensive attention. In this work, the possibility of halogen bonding of neutral and anionic forms of para‐substituted iodine derivatives of dithiobenzoic acid and its Se‐ and Te‐based congeners with halide anions has been investigated. The anion‐anion complexes are not favorable in the gas phase because of the repulsive effect between anionic halogen bond donors and acceptors. A local minimum is present in the potential energy surface between the − S2 CC6 H4 I and X (X=F −, Cl −, Br − ), and the anion‐anion complexes − S2 CC6 H4 I ⋅⋅⋅ X(X=F −, Cl −, Br − ) are metastable in the gas phase. Solvation is beneficial to the formation of the anion‐anion complexes. The neutral‐anion complexes are stable in both the gas phase and the polar solvents. The anion‐anion halogen bonds tend to be stable in polar solvents, while the neutral‐anion halogen bonds are stronger in the gas phase than in solvents. Abstract : A question of stability : Halogen bonds in anion‐anion complexes and neutral‐anion complexes were evaluated in the gas phase and polar solvents. The neutral‐anion complexes are stable in both the gas phase and polar solvents, although neutral‐anion halogen bonds are stronger in the gas phase than in solvents. Anion‐anion complexes − S2 CC6 H4 I ⋅⋅⋅ X(X=F −, Cl −, Br − ) are metastable in the gas phase and the anion‐anion halogen bonds tend to be stable in polar solvents.